A Survey on Internet Security Threat in Malaysia’s Internet Banking System and Suggestion Solutions - Mohd Hariz, Ibrahim; Mohd Sarifuddin, Othman@Mustafa; Mokhtar Esmail, Mufadal; Kohbalan, Moorthy; Mohd Azwan, Mohamad (Publishing Technology, 2018)
This paper does review of survey and analysis on security features and methodology on reviewing other journal papers. This survey paper was focusing on internet security threat and issues in an internet banking system in Malaysia. The security features on this samples journal was analyzed and compared to common features provided on internet banking in Malaysia. The procedure was created to show the weaknesses and advantages of internet security system for concerning new knowledge of security level that provide by samples of bank. The analyses and discussion was made to propose security enhancement with the best suggestion solution.